Kesenian Tradisional Sebagai Sarana Strategi Kebudayaan di Tengah Determinasi Teknologi Komunikasi - Agus Maladi Irianto (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
Traditional art in this paper is seen as cultural identity for its supported community, that has a specific role socially and ritually. The supported community, in addition, believes that this traditional art is not only acted as an entertainment, but also a facilitator for their hopes and prays. Despite some changes have influenced the differences of style and variation in the performing art, however, the changes themselves are the manifestation of adaptive strategy had from the supported community to preserve and conservetraditional art. Determination of communications technology or the exposure of communications technology present in the midst of society and influence the worldview and human behavior in everyday life.